Awareness of PERMATA@Pintar Negara Centre Students about Bingo Game as Aid Tool in Teaching and Learning - Nur Shamim Hamzah; Ku Aqhlan Hafiey Ku Aznal Shahri; Siti Munirah Mohd (Kolej PERMATA Insan, 2025)
International Conference And Innovation On Education, Science & Technology (ICIEST 2025) “Fostering Innovation And Creativity Through Education, Science & Technology” 21st June 2025 Editor : Hatika Kaco, Diani Mardiana Mat Zin, Fadzidah Mohd Idris, Siti Munirah Mohd Nurhidaya Mohamad Jan, Nor Atirah Izzah Zulkefli, Nadiah Suboh Organised by : Education & Advanced Sustainability (EdAS) unit, Kolej PERMATA Insan, Universiti Sains Islam Malaysia